O trabalho do assistente social na atenção básica em saúde em Sergipe (2015 a 2019) - Mendonça, Isabelle Pinto (2020)
In Brazil, health is a right guaranteed by the State and guaranteed by the Federal Constitution of 1988 through the Unified Health System (SUS), which was regulated by Law 8.080 / 1990. Historically, the 1990s were also marked by the entry of neoliberalism in the country, a fact that brought impacts to the health area, resulting in a recession of the rights acquired by society. Parallel to these events, globalization has gained prominence on the world stage, integrating different countries through a network of technology and communication systems. At the national level, the effects of globalization were felt in various sectors and policies. This was the case with public health, which adopted the use of technologies to implement the decentralized management of its services. Currently, the Ministry of Health is executing the so-called: "Digital Health Strategies", with the objective of implementing and improving the management of care in the area. The Federal Government has been investing in health information systems, focusing especially on the National Primary Care Policy, as this level of care is configured as the “main door” for citizens to access the country's integrated care network. In this sense, it aims to qualify the Health Policy through work from the base of SUS, using information and communication technologies (TIC). In primary health care, the SISAB and SIA / SUS systems are also responsible for communicating about the work process developed by professionals. In view of this observation, this study aimed to: analyze the work of social workers in primary health care in Sergipe from 2015 to 2019. To follow this path, the methodology adopted was a descriptive, empirical, exploratory study, with quali-quantitative approach, through the historical-dialectical materialism method. As for the results, seven analysis variables were used that communicated about the work of the social worker, being among the main results: the health region of Aracaju, which had the highest rates (94%) of records of this professional's performance; health education (90%), which was the predominant response in the form of work organization; the UBS space (86%) that stood out as to the service location and, among the work procedures, health promotion and prevention actions were the most constant (90%). This research fulfilled the proposed objectives, highlighting the potential of health information systems, especially SISAB and SIA / SUS, to communicate about the work of the social worker in a way connected with reality, clearly reflecting on the performance of this level of primary health care. In view of the above, it was concluded that health information systems are important management and social control tools, with the capacity to capture the production of social worker work and make available to the whole society as an official data of the Brazilian State, contributing thus for the construction of the social image of the profession.